EXTREME STATES: A SHOCK - P.F. Litvitsky ("Paediatrician" Publishers LLC, 2010)
The lecture analyzes etiology and key parts of pathogenesis of a form of extreme states - a shock. Author characterizes its types and symptoms and principles of treatment and prophylaxis. Key words: sludge, disseminated formation of thrombus and fibrinolysis, «shock lungs», «shock kidney». (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):85-93)